2014
DOI: 10.1158/1055-9965.epi-13-1219
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of Volumetric Mammographic Density: A Tool for Widespread Breast Cancer Risk Assessment

Abstract: Introduction: Mammographic density is a strong risk factor for breast cancer and an important determinant of screening sensitivity, but its clinical utility is hampered due to the lack of objective and automated measures. We evaluated the performance of a fully automated volumetric method (Volpara).Methods: A prospective cohort study included 41,102 women attending mammography screening, of whom 206 were diagnosed with breast cancer after a median follow-up of 15.2 months. Percent and absolute dense volumes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Park et al evaluated VPD with Volpara as a risk factor among Korean women (n = 677 cases) and found associations of similar magnitude to those in our study among postmenopausal women (22). Brand et al (28) found VPD and DV, estimated with Volpara on mammograms a median of 22 days from cancer diagnosis, to be associated with breast cancer in a cohort study, with 206 incident cases (28). The magnitude of risk between the highest and lowest quartiles of VPD in the lower but positive risk estimates when using quintiles of density (OR, 2.6 with Volpara and 2.0 with Quantra).…”
Section: Breast Imaging: Comparison Of Clinical and Automated Breast supporting
confidence: 86%
See 1 more Smart Citation
“…Park et al evaluated VPD with Volpara as a risk factor among Korean women (n = 677 cases) and found associations of similar magnitude to those in our study among postmenopausal women (22). Brand et al (28) found VPD and DV, estimated with Volpara on mammograms a median of 22 days from cancer diagnosis, to be associated with breast cancer in a cohort study, with 206 incident cases (28). The magnitude of risk between the highest and lowest quartiles of VPD in the lower but positive risk estimates when using quintiles of density (OR, 2.6 with Volpara and 2.0 with Quantra).…”
Section: Breast Imaging: Comparison Of Clinical and Automated Breast supporting
confidence: 86%
“…There are several limitations of this study, including the fact that we study of Brand et al was similar to ours (OR of 2.9 and 2.8, respectively) (28).…”
Section: Breast Imaging: Comparison Of Clinical and Automated Breast mentioning
confidence: 45%
“…However, Cumulus suffers from the same shortcomings as BI-RADS. Use of mammographic density in future risk prediction models will benefit from fully automated programs for measurement of mammographic density, such as the Volpara program (40,41). Compared with BI-RADS, advantages of automated systems include objectivity in measures and a continuous scale from which the entire spectrum of density values can provide information.…”
Section: Prevention Trials and Clinical Programsmentioning
confidence: 99%
“…These algorithms can be highly nonlinear and are highly proprietary. The effect of this on MD was assessed recently by Brand et al 17 They conducted a comparative study using Volpara on five different mammographic imaging systems assessing breast cancer risk with automated measurement. The authors reported that with the exclusion of the small GE detector, minor differences were noted between GE, Phillips, and Sectra systems, with the largest relative difference in percent dense volume being 3%.…”
Section: Introductionmentioning
confidence: 99%